Manufacturing firms' reliance on past or future sales information in inventory production: an international study / Haihong He - He, Haihong (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
This study examines whether manufacturing firm's preference for use of past or future period sales information in determining inventory production is associated with two country level variables - management control system score and shareholder protection level. This study uses archival data to empirically examine the association between inventory production and sales information across twenty countries with different management control system score measured by Bloom et al. (2012) and different shareholder protection level measured by La Porta et al. (1997, 1998) and Djankov et al. (2008). This study finds that the entire sample experience a positive association between current period inventory production and future period sales change and no association between current period inventory production and past period sales change, suggesting that firms generally use future or projected sales change information instead of past sales change information in making production decisions. The study further shows that, after partitioning the sample based on country characteristics, the reliance on the future sales change information appears greater when firms are in countries with low management control system score or with high shareholder protection level. This study uses a large sample to gauge systematic differences in the use of management accounting information in inventory production across countries. The results suggest that less emphasis on management control (which may indicate greater emphasis on decision making) and high shareholder protection level have a positive effect on the firm's preference of future information.